Method for improving drying efficiency of micro-nano copper powder based on freeze-drying area
By adjusting the freeze-drying area and optimizing the vacuum freeze-drying conditions, the problems of high moisture content and degradation of performance of micro-nano copper powder during the drying process are solved, and the effects of efficient drying, low energy consumption and performance maintenance are achieved.
Patent Information
- Application Number
- CN202411981648.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
Micro-nano copper powder is easy to absorb and retain moisture during the drying process, resulting in reduced performance and limited application effects. Existing drying methods such as hot air drying and microwave drying have poor uniformity, high energy consumption and risk of oxidation reactions.
By adjusting the freeze-drying area, the vacuum freeze-drying conditions are optimized, including controlling the pressure and temperature, improving the drying efficiency, reducing energy consumption, and preventing oxidation reactions.
It improves the drying efficiency of micro-nano copper powder, reduces energy consumption, maintains material performance, improves product quality, and meets the needs of high-end application fields.
Smart Images

Figure BDA0005221691500000061 
Figure BDA0005221691500000071 
Figure BDA0005221691500000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powder material preparation, and in particular relates to a method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area. Background Art
[0002] Micro-nano copper powder, with its extraordinary physical properties and chemical activity, has shown extremely broad and attractive application prospects in many fields such as the manufacture of cutting-edge electronic devices, the research and development of military technology, and the exploration of biomedical engineering. However, in the fine preparation process of micro-nano copper powder, a tricky problem is that it easily absorbs and retains moisture. This phenomenon not only significantly weakens its inherent performance advantages, but also greatly limits its performance and effect in practical applications. For this reason, the drying process occupies a pivotal position in the entire preparation process of micro-nano copper powder, which is directly related to the quality and stability of the final product.
[0003] Looking back, people have tried and applied a series of traditional drying methods to meet the dehumidification needs of micro-nano copper powder, such as hot air drying and microwave drying. Although these traditional methods can indeed reduce the moisture content of micro-nano copper powder to a certain extent, unfortunately, they are also accompanied by a series of problems that are difficult to ignore: hot air drying often cannot ensure the uniformity of the drying process, resulting in the possibility of residual moisture inside the product; microwave drying increases production costs due to high energy consumption and high equipment requirements; more importantly, these drying methods are very likely to cause oxidation reactions when processing micro-nano materials, thereby further damaging the performance of the materials.
[0004] In contrast, vacuum freeze-drying technology, with its unique drying mechanism, provides a more ideal choice for the drying treatment of micro-nano copper powder. Through precise control, this technology first freezes the material to be dried to a low temperature state below its eutectic point, and then uses the sublimation principle in a strictly controlled low temperature and low pressure environment to directly convert the frozen water in the material into steam and discharge it, thereby achieving the purpose of removing moisture. This method not only ensures the uniformity and efficiency of the drying process, but also effectively avoids the occurrence of oxidation reactions because the entire process is carried out under vacuum and low temperature conditions, thereby greatly improving the quality of the product. However, although vacuum freeze-drying technology has shown significant advantages in the drying treatment of micro-nano copper powder, there is currently a lack of systematic and in-depth research in academia and industry on the specific impact of the key parameter of freeze-drying area on drying efficiency and final moisture content. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area, which can at least improve the drying efficiency by adjusting the freeze-drying area.
[0006] The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area comprises cooling and freezing the prepared wet micro-nano copper powder, performing vacuum freeze drying at different freeze-drying areas, testing the moisture content of the dried micro-nano copper powder obtained at different times and different freeze-drying areas, and optimizing the freeze-drying area.
[0007] Furthermore, the wet micro-nano copper powder is wet copper powder that has been centrifuged 1 to 6 times and has a particle size of 0.01 μm-40 μm.
[0008] Furthermore, the wet powder of the micro-nano copper powder is 1g to 500g.
[0009] Furthermore, the cooling and freezing includes liquid nitrogen freezing or vacuum freeze drying machine pre-freezing.
[0010] Furthermore, the freeze-drying area is adjusted by controlling the size, quantity and layout of the shelves in the vacuum freeze dryer.
[0011] Furthermore, the freeze-drying area is 10 cm 2 ~25cm 2 The freeze-drying time is 16h to 18h.
[0012] Furthermore, during the vacuum freeze-drying process, the pressure is 0.009 bar to 0.011 bar, and the temperature is -58°C to -62°C.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The invention proposes a method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area, which improves the drying efficiency, reduces energy consumption, maintains material properties and improves product quality by changing the freeze-drying area and optimizing the drying conditions. DETAILED DESCRIPTION
[0015] The present invention is further described below through specific embodiments in conjunction with the accompanying drawings, but the present invention is not limited thereto. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0016] definition:
[0017] Micro-nano copper powder: The micro-nano copper powder in the present invention refers to copper powder with a particle size ranging from micron (μm) to nanometer (nm), generally including ultrafine copper powder, submicron copper powder and nano copper powder.
[0018] Micrometer is a unit of length, symbolized by μm, and 1 micrometer is equivalent to one millionth of a meter. Micron-grade copper powder refers to copper powder with a particle size ranging from one micrometer to several hundred micrometers. Nanometer is a unit of length, symbolized by nm, and 1 nanometer is equal to 0.001 micrometer. Nano copper powder refers to a particle size below 0.1 micrometer, that is, a size below 100 nanometers. The ultrafine copper powder in the present invention refers to copper powder with a very small particle size. It is generally believed in the market that copper powder with a size of ≤20 micrometers belongs to ultrafine copper powder. Submicron copper powder refers to a series of ultrafine powders from micron to nanometer. The submicron copper powder in the present invention refers to metal powder with a particle size ranging from 0.1 micrometer to 10 micrometers.
[0019] Solid solution or gel: The solid solution or gel in the present invention refers to the solid solution or gel formed by freezing the wet powder of micro-nano copper powder, which refers to the state of the wet powder of micro-nano copper powder after centrifugal washing after rapid cooling and freezing by liquid nitrogen. The solid solution formed by freezing the wet powder of micro-nano copper powder can be in liquid form or semi-fixed form according to the freezing time and freezing temperature. The gel formed by freezing the wet powder of micro-nano copper powder is in a semi-solid state.
[0020] A method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area comprises the following steps:
[0021] S1: cooling and freezing the prepared wet micro-nano copper powder in a low temperature environment to form a frozen product;
[0022] First, prepare the wet powder of micro-nano copper powder: by liquid phase chemical reduction method but not limited to, and then use centrifugal washing method to prepare wet powder of micro-nano copper powder (hereinafter referred to as wet copper powder). The centrifugal washing method is to perform centrifugal washing by a desktop high-speed centrifuge. The centrifuge in the present invention adopts the high-speed desktop centrifuge of model TG16.5 produced by Shanghai Lu Xiangyi Centrifuge Instrument Co., Ltd., but is not limited to this manufacturer and this model of centrifuge equipment. The centrifugal washing is performed 1 to 6 times to achieve the purpose, thereby ensuring that a large amount of water in the wet powder of micro-nano copper powder has been removed. In actual centrifugal washing, other types of centrifuges that can ensure that a large amount of water in the wet powder of micro-nano copper powder has been removed can also be used. The obtained micro-nano copper powder wet powder refers to wet copper powder that has been centrifuged 1 to 6 times and has a particle size of 0.01μm to 40μm. Specifically, the dried copper powder is subjected to a particle size test to take its D50 value for comparison with the particle size of the wet copper powder. A laser particle size analyzer, such as the Bettersize2600 laser particle size analyzer produced by Dandong Bettersize Instrument Co., Ltd., or other manufacturers and other types of particle size detection equipment, is used to test the particle size of the obtained wet copper powder, thereby selecting wet copper powder with a particle size of 0.01μm to 40μm, and the wet copper powder is 1g to 500g.
[0023] Then freeze the wet micro-nano copper powder: use the prepared wet micro-nano copper powder as a precursor to cool and freeze in a low temperature environment to form a solid solution or gel. The wet micro-nano copper powder is cooled and frozen in a low temperature environment, and the frozen product formed is a solid solution or gel formed by freezing the wet micro-nano copper powder. Freezing the wet micro-nano copper powder can be achieved by rapid freezing with liquid nitrogen. Rapid freezing with liquid nitrogen refers to rapid freezing using liquid nitrogen freezing equipment in the prior art. The cooling and freezing process is not limited to a vacuum freeze dryer, and can also be other equipment that can freeze the wet micro-nano copper powder into a solid solution or gel. The present invention uses a vacuum freeze dryer model LGJ-10 of Beijing Songyuan Huaxing Technology Development Co., Ltd., or other equipment not limited to this manufacturer or this model to achieve the pre-freezing function.
[0024] S2: placing the formed frozen material in a vacuum freeze dryer, and performing freeze drying at different freeze drying areas, and obtaining dry micro-nano copper powder by controlling pressure and temperature; testing the moisture content of the dry micro-nano copper powder obtained at different times and different freeze drying areas, and optimizing the freeze drying area.
[0025] The freeze-dried area refers to the area between 0 and 30 cm when the thickness of the fabric remains unchanged (within the range of 0 to 10 mm). 2 The freeze-drying area is set by adjusting the size, quantity and layout of the shelves in the vacuum freeze dryer.
[0026] Freeze drying is performed under different freeze drying areas. In the embodiment of the present invention, the frozen solid solution or gel is placed on the shelf of the freeze dryer, and the freeze drying area is changed by adjusting the size, number and layout of the shelf in the freeze dryer. 2 ~25cm 2 The frozen material is freeze-dried under the conditions of a pressure of 0.009 bar to 0.011 bar and a temperature of -58°C to -62°C, so that the water in the frozen material is directly sublimated into steam, thereby obtaining dry micro-nano copper powder.
[0027] The moisture content of the dried micro-nano copper powder obtained at different times and different freeze-drying areas is tested. When optimizing the freeze-drying area, the moisture content of the dried micro-nano copper powder is first tested, and the moisture content of the micro-nano copper powder at different times and different freeze-drying areas is recorded. The moisture content of the micro-nano copper powder can be tested by selecting a rapid halogen moisture determination method, a Karl Fischer method, a resistance heating drying weight loss method, and the like.
[0028] Then, according to the test results, the freeze-drying area with the lowest moisture content and the highest drying efficiency was selected as the optimal freeze-drying area.
[0029] For nano copper powder with poor antioxidant properties and smaller particle size (with heat generation), the moisture content is generally high after a method of improving the drying efficiency of micro-nano copper powder based on freeze-drying area. The drying time of the micro-nano copper powder is 6h to 18h. The optimized freeze-drying area is based on the same freeze-drying time, and the freeze-drying area with the lowest moisture content test result and the highest drying efficiency is selected as the optimal freeze-drying area.
[0030] A method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area has the following advantages:
[0031] 1. Improve drying efficiency: By adjusting the freeze-drying area, the drying conditions can be optimized, the drying efficiency can be improved, and the drying time can be shortened.
[0032] 2. Reduce energy consumption: The optimized freeze-drying area can reduce unnecessary energy consumption and reduce production costs.
[0033] 3. Maintain material properties: Vacuum freeze-drying technology can effectively prevent the oxidation and agglomeration of micro-nano copper powder and maintain its original structure and properties.
[0034] 4. Improve product quality: By precisely controlling the freeze-drying area, micro-nano copper powder with low moisture content and excellent performance can be obtained to meet the needs of high-end application fields.
[0035] Example 1
[0036] S1: Prepared by liquid phase chemical reduction method, and then centrifuged and washed 4 times by centrifuge to obtain wet micro-nano copper powder with a particle size of 0.01 μm to 40 μm, i.e. wet copper powder, weighing 50 g of wet copper powder;
[0037] S2: Adjust the size, quantity and layout of the shelves in the vacuum freeze dryer to change the freeze-drying area. 2 ~25cm 2 The solid solution or gel is formed by rapid freezing with liquid nitrogen at different freeze-drying areas. The formed frozen product is placed in a vacuum freeze dryer, and the pressure is controlled to be 0.01 bar and the temperature is -60°C. Freeze drying is performed within this range. The drying time of the micro-nano copper powder is controlled within the range of 6h to 18h, and dried micro-nano copper powder is obtained after drying. The moisture content of the dried micro-nano copper powder obtained at different times and different freeze-drying areas is tested to optimize the freeze-drying area.
[0038] Table 1 below shows the moisture content test data of micro-nano copper powder at different drying times under the conditions of Example 1.
[0039] Table 1:
[0040]
[0041] It can be seen from the table above that as the freeze-drying area increases and the freeze-drying time increases, the drying efficiency is greatly improved. 2 ~25cm 2 , under the drying conditions of freeze-drying time of 16h to 18h, the drying efficiency can be effectively improved.
[0042] Example 2
[0043] S1: Prepared by liquid phase chemical reduction method, and then centrifuged and washed 4 times by centrifuge to obtain wet micro-nano copper powder with a particle size of 0.01 μm to 40 μm, i.e. wet copper powder, weighing 100 g of wet copper powder;
[0044] S2: Adjust the size, quantity and layout of the shelves in the vacuum freeze dryer to change the freeze-drying area. 2 ~25cm 2 The solid solution or gel is formed by rapid freezing with liquid nitrogen at different freeze-drying areas. The formed frozen product is placed in a vacuum freeze dryer, and the pressure is controlled to be 0.01 bar and the temperature is -60°C. Freeze drying is performed within this range. The drying time of the micro-nano copper powder is controlled within the range of 6h to 18h, and dried micro-nano copper powder is obtained after drying. The moisture content of the dried micro-nano copper powder obtained at different times and different freeze-drying areas is tested to optimize the freeze-drying area.
[0045] Table 2 below shows the moisture content test data of micro-nano copper powder at different drying times under the conditions of Example 2.
[0046] Table 2:
[0047]
[0048] It can be seen from the table above that as the freeze-drying area increases and the freeze-drying time increases, the drying efficiency is greatly improved. 2 ~25cm 2 , under the drying conditions of freeze-drying time of 16h to 18h, the drying efficiency can be effectively improved.
[0049] Example 3
[0050] S1: Prepared by liquid phase chemical reduction method, and then centrifuged and washed 4 times by centrifuge to obtain micro-nano copper powder with a particle size of 0 μm to 40 μm, i.e. wet copper powder, weighing 500 g of wet copper powder;
[0051] S2: Adjust the size, quantity and layout of the shelves in the vacuum freeze dryer to change the freeze-drying area. 2 ~25cm 2The solid solution or gel is formed by rapid freezing with liquid nitrogen at different freeze-drying areas. The formed frozen product is placed in a vacuum freeze dryer, and the pressure is controlled to be 0.01 bar and the temperature is -60°C. Freeze drying is performed within this range. The drying time of the micro-nano copper powder is controlled within the range of 6h to 18h, and dried micro-nano copper powder is obtained after drying. The moisture content of the dried micro-nano copper powder obtained at different times and different freeze-drying areas is tested to optimize the freeze-drying area.
[0052] The following table shows the test data of moisture content of micro-nano copper powder at different drying times under the conditions of Example 3.
[0053] Table 3:
[0054]
[0055] It can be seen from the table above that as the freeze-drying area increases and the freeze-drying time increases, the drying efficiency is greatly improved. 2 ~25cm 2 , under the drying conditions of freeze-drying time of 16h to 18h, the drying efficiency can be effectively improved.
Claims
1. A method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area, characterized in that: The prepared wet micro-nano copper powder is cooled and frozen, and vacuum freeze-dried at different freeze-drying areas. The moisture content of the dried micro-nano copper powder obtained at different times and different freeze-drying areas is tested to optimize the freeze-drying area.
2. The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area according to claim 1, characterized in that: The wet micro-nano copper powder is wet copper powder that has been centrifuged 1 to 6 times and has a particle size of 0.01 μm to 40 μm.
3. The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area according to claim 1 or 2, characterized in that: The wet powder of the micro-nano copper powder is 1g to 500g.
4. The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area according to claim 3, characterized in that: The cooling and freezing includes liquid nitrogen freezing or vacuum freeze drying machine pre-freezing.
5. The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area according to any one of claims 1 to 4, characterized in that: The freeze-drying area is adjusted by controlling the size, quantity and layout of the shelves in the vacuum freeze dryer.
6. The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area according to claim 5, characterized in that: The freeze-drying area is 10 cm 2 ~25cm 2 The freeze-drying time is 16h to 18h.
7. The method for improving the drying efficiency of micro-nano copper powder based on freeze-drying area according to any one of claims 1 to 6, characterized in that: During the vacuum freeze-drying process, the pressure is 0.009 bar to 0.011 bar, and the temperature is -58°C to -62°C.